Research Dissemination and Impact: Evidence from Web Site Downloads - Pinkowitz, Lee (Journal of Finance, 2002)
ABSTRACT The Journal of Finance Web site disseminates research expediently to a broad audience. Papers were downloaded 284,170 times from November 1997 to November 1999. The average paper receives 85 downloads per month and is available 10 months before publication. Articles are downloaded more than shorter papers. Lead articles are downloaded more than other articles because they are of greater interest, and they receive an endorsement as the lead. Downloads are positively correlated with citations and may be a useful measure of research impact. Finally, placing forthcoming articles online does not adversely affect subscriptions and may increase the SSCI impact factor.